2021
DOI: 10.1021/acs.inorgchem.1c02062
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Cu-Based Metal–Organic Framework by Employing a Mixed-Ligand Strategy and Its Facile Conversion into Nanofibrous CuO for Electrochemical Energy Storage Applications

Abstract: Recently, metal–organic frameworks (MOFs) have been widely employed as a sacrificial template for the construction of nanostructured materials for a range of applications including energy storage. Herein, we report a facile mixed-ligand strategy for the synthesis of a Cu-MOF, [Cu3(Azopy)3(BTTC)3(H2O)3·2H2O] n (where BTTC = 1,2,4,5-benzenetetracarboxylic acid and Azopy = 4,4′-azopyridine), via a slow-diffusion method at room temperature. X-ray analysis authenticates the two-dimensional (2D)-layered framework o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 98 publications
0
17
0
Order By: Relevance
“…29 Rajak et al derived CuO from Cu-MOF and utilized it for a supercapacitor, further achieving a specific capacitance of 244.2 F g −1 with a cyclic retention of 63.3% after 1500 cycles. 30 In recent progress, various engineering strategies have been utilized to synthesize a highly efficient OER electrocatalyst. In this regard, Hu et al utilized various vacancy engineering strategies on ZIF-67-based MOF via selenic acid etching to achieve high catalytic active sites and improved conductivity in an electrocatalytic system with a low overpotential.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Rajak et al derived CuO from Cu-MOF and utilized it for a supercapacitor, further achieving a specific capacitance of 244.2 F g −1 with a cyclic retention of 63.3% after 1500 cycles. 30 In recent progress, various engineering strategies have been utilized to synthesize a highly efficient OER electrocatalyst. In this regard, Hu et al utilized various vacancy engineering strategies on ZIF-67-based MOF via selenic acid etching to achieve high catalytic active sites and improved conductivity in an electrocatalytic system with a low overpotential.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Various MOF-derived and MOF hybrid materials were explored for supercapacitors and OER activity; for instance, Devi et al prepared a Co-MOF-derived Co/N-doped carbon structure utilized for the supercapacitor that further achieved a specific capacitance of 310 F g –1 with a cyclic retention of 87% after 1200 cycles . Rajak et al derived CuO from Cu-MOF and utilized it for a supercapacitor, further achieving a specific capacitance of 244.2 F g –1 with a cyclic retention of 63.3% after 1500 cycles . In recent progress, various engineering strategies have been utilized to synthesize a highly efficient OER electrocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…26 Since then, many MOF-based electrodes have been reported. 27–57 Very recently, Chen et al synthesized a conductive 3D conjugated copper( ii ) catecholate based MOF (Cu-DBC) and found that it can deliver superior capacitive performances (479 F g −1 at 0.2 A g −1 ). 47 Although much progress has been made in MOF-based electrodes, the used organic linkers are usually costly, seriously restricting their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The efficient use of clean energy sources needs to be matched with high-performance energy storage and conversion systems due to solar energy and wind energy being intermittent. , As one kind of important energy storage system, supercapacitors possess the characteristics of a high power density and long cycle stability but lower energy density. To overcome the shortcoming of low energy density and extend the application fields of supercapacitors, various electrode materials have been developed in recent years. Among them, coordination polymers (CPs), especially porous CPs/metal–organic frameworks (MOFs), directly as the electrode materials, have received considerable interest, owing to the porosity and redox-active metal ions/organic ligands in them. Coordination polymers include three kinds of branches, one-dimensional (1D) CPs, two-dimensional (2D) CPs, and three-dimensional (3D) CPs. Many 2D and 3D CP/MOF-based electrode materials for supercapacitors have been reported.…”
Section: Introductionmentioning
confidence: 99%